Local administration of AD.VEGF-A165 to the utero-placental circulation reduces brain sparing and may enhance fetal growth in an FGR model of guinea pig pregnancy. (18th April 2012) - Mehta, V; Boyd, M; Barker, H; Avdic-Belltheus, A; Carr, D; Martin, J; Zachary, I; Peebles, DM; David, AL
Abstract : Introduction: Fetal growth restriction (FGR) is commonly caused by impaired utero-placental perfusion. Adenovirus (Ad) mediated over-expression of VEGF-A165 in the uterine arteries (UtAs) of pregnant sheep significantly increases UtA blood flow, compared with UtAs transduced with a control adenovirus encoding β-galactosidase (Ad.LacZ). In FGR sheep, UtA injection of Ad.VEGF-A165 significantly improves fetal growth velocity. Aim: To study if Ad.VEGF-A165 transduction enhances fetal growth in the FGR guinea pig. Methods: To create FGR, virgin Dunkin-Hartley guinea pigs were nutrient restricted peri-conceptually. Under general anaesthesia at mid-gestation (30-34 days), sonographic fetal measurements were recorded in FGR guinea pigs and control ad lib fed sows. At laparotomy the UtAs and radial arteries on each side were transduced externally with Ad.VEGF-A165 or Ad.LacZ (5x10 9 viral particles), using a thermosensitive pluronic gel. Guinea pigs were sacrificed 31-34 days post-surgery but before birth. Fetal organ weights and biometry were recorded. Results: Nutrient restriction reduced fetal weight by 40%, with brain sparing. In FGR pregnancies, administration of Ad.VEGF-A165 increased fetal weight(94.5 ± 2.01g, n=11) compared to control Ad.LacZ treated fetuses (84.9 ± 2.81g, n=10, p=0.061). The liver and kidneys were significantly heavier in the Ad.VEGF-A165 group (5.6 ± 0.23g v/s 4.7 ± 0.18g, p=0.019 and 0.74 ± 0.065g v/s 0.37 ± 0.021g, p<0.001 respectively), and the brain/liver weight ratio was significantly lower (0.45 ± 0.019 v/s 0.53 ± 0.017, p=0.021), suggesting an attenuated brain sparing effect. Conclusion: VEGF gene therapy targeted to the utero-placental vasculature reduces brain sparing and may enhance fetal growth in FGR guinea pig pregnancy, and is a potential treatment for severe FGR.